INFLUENCE OF FOREIGN AID ON POLITICAL DEVELOPMENT IN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study has been explicitly on the nature of perception that the citizen harbors towards foreign aid impact on South Sudan political development. It engulfs teachers’ and the stakeholders’ perception as key holders in foreign affair office and IDP leader. The study methods were based on interviews, focus group discussion and observation. The literatures were reviewed from various books, thesis and published articles in relation to the study. The finding of the study gives a clear indication on the positive and the negative way foreign aid perceived and value in political development According to the finding and analysis, majorities 92% of the candidates were not hoping to become refugee or IDP as they were interested in other activities that can bring for them food as other people only fear for their life that why they found them been fed like young children that they said they may hope for good and secure system of government, and they will be productive too to the country. This study therefore gives alert to the stakeholders in the government and the citizen that there is need  to start rethinking on a better way in which we can solve our from not to create more and get exactly what is the root cause our problem and get proportional solution,  people are crying for real freedom not position  which can make the country attractive so that citizen can leave negative feeling toward the toward their government and the country as well. However, this thesis endeavored to discuss along sides the point of compromise in whichthe respondents were both positive and negative in their perception toward impact of foreign aid on political development.  The findings indicated that there were more negative perceptions toward foreign aid especially during this  period of conflict that people said the aid that is coming for development is being divert for buying military equipment to fight and perception have brought questions in the mind of the citizen and answer is event not there but no hope for life and the future of the country unpredictable, based on the data government should provide security for the people so that citizen go and do economic activities which can help the government to do developmental activities for the country. Over the previous two decades, humanitarian aid has focused more on the protection of vulnerable people. When disasters hit populations, vulnerabilities increase. International aid is important because it allows humanitarian actors and local organizations to run projects that can protect people who are especially vulnerable as a result a crisis.Humanitarian protection works to ensure all people affected by crises can access their full rights. This is especially vital for population groups such as women, children, disabled or minorities. Humanitarian aid is important because it allows for work to be done to protect such vulnerable groups.To ensure all people, retain access to their rights during a humanitarian emergency, it is important that international aid actors can mobilize and operate effectively. As impartial and neutral organizations, humanitarian agencies are vital in protecting marginalized individuals and groups. This is a major example of the importance of humanitarian work but that serviced by the humanitarian aid is not enough for South Sudan to developed strong in political arena aid always have string attachment.The data collection from the field indicates for me that When people are hit by crises, conflicts or disasters, they lose their livelihoods, aid is important because it can assist people with rebuilding their livelihoods and business, returning to being able to provide for their family and community. Livelihoods projects are a key part of many humanitarian responses.Without humanitarian assistance, many communities may never recover economically from a crisis. Humanitarian aid can play a vital part in helping people recover through projects designed to re-establish businesses and provide jobs. This is one of major ways international aid is important.There are many types of humanitarian livelihood projects. These include cash distributions, cash for work, business micro-finance and providing resources and tools for livelihood development. Helping people to recover their work, jobs and business after a disaster is crucial if communities are to recover and humanitarian aid plays a vital part.